Testate Amoebae (Amebozoa: Arcellinida) in Tropical Lakes of Central Mexico - Sigala, Itzel (2016)
Testate amoebae are common single-celled eukaryotic organisms in aquatic ecosystems. Despite their important role in these ecosystems, and their potential as bioindicators and paleoindicators, they remain poorly studied in Mexico. The major objectives of this study were to: 1) increase knowledge of testate amoebae in Mexico’s tropical lakes, and 2) create a catalog of high-quality scanning electron micrographs that can be used for future ecological and paleoenvironmental studies. We collected surface-sediment samples from 29 lakes, located in the Transmexican Volcanic Belt, one at each lake during June and October 2011, and March 2013. Sediments were collected with an Ekman grab and preserved in anhydrous ethanol. Sub-samples were observed under a stereomicroscope and morphometric data for each species were recorded. Total diameter and aperture diameter were measured on circular tests. Irregularly shaped tests were measured for length and width of the aperture and for the size of the whole test. If a specimen possessed spines, the length of one randomly selected spine was measured. The best-preserved specimen of each taxon was photographed with an optical microscope and a scanning electron microscope (SEM). We found 41 taxa of testate amoebae belonging to the genera: Arcella, Centropyxis, Cucurbitella, Cyclopyxis, Cyphoderia, Difflugia, Euglypha, Lesquereusia, Pentagonia, Pseudodifflugia and Scutiglypha. Twelve species not previously reported for Mexico were recorded, along with 13 varieties. The average number of taxa recorded in each lake was eight, and the highest taxonomic richness was 18. The taxon found in the greatest number of lakes was Centropyxis aculeata var. aculeata. Taxonomic richness varied among lakes in the same region. This could reflect lake-specific differences in environmental conditions, underscoring the need for more detailed studies that include collection of data on physical and chemical variables in the lakes. Our results highlighted the need of further studies for the distribution patterns and ecology of lacustrine testate amoebae.